RECHTSVACUUM ATAS TANGGUNGJAWAB PEMBINA YAYASAN - Miarsa, Fajar Rachmad Dwi; hazir, cholilla adhaningrum (Lex Librum : Jurnal Ilmu Hukum, 2021)
The foundation is a legal entity that is private and run without profit (profit oriented). There are three organs that run a Foundation, namely Builders, Managers and Supervisors. The organ that is responsible for running the Foundation so that the purpose and purpose of the foundation of the Foundation which is social, religious, and humanitarian can be realized. Establishment of Law Foundation Number 16 of 2001 on the Foundation. The regulation contains the norm vacancy (rechtsvacuum) in the regulation of Foundation Builders. The problematic form of authority possessed by the Founders of the Foundation, seems to be infinite (absolute) and there is no arrangement for the termination of the Builder. The purpose of this writing is to analyze the form of vacancy norms of Law No. 16 of 2001 on the Foundation regarding the authority held by the Founders of the Foundation. Based on the description, then the problem is what are the consequences of juridis rechtsvacuum on Law Number 16 of 2001 on the Foundation on the form of responsibility of the Builder ?. This writing uses the writing method used is the normative juridical writing that is all the activities of a person to answer legal issues that are academic and practical, using a legal approach (Statute Approach), and a conceptual approach (Conceptual Approach) with prescriptive writing that gives a description or formulate problems in accordance with existing circumstances / facts. The author uses this method to provide an argument for the results of the writing done by the author. The results of the writing on the legal consequences of the form of problem solving on the form of arbitrariness of the Founders of the Foundation due to the vacancy of rules (rechtsvacuum) on Law No. 16 of 2001 on the Foundation.